Analisis Implementasi Sistem Pengendalian Intern Pemerintah (SPIP) Pada Pemerintah Daerah Kota Cimahi - Via Nur Anisa; Ahmad Syarief (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study aims to determine the implementation of the Government Internal Control System (SPIP) in the Regional Government of Cimahi City based on Peraturan Pemerintah No. 60 Tahun 2008 concerning Government Internal Control System (SPIP) and the implementation constraints based on the five elements of SPIP, namely control environment, risk assessment, control activities, information and communication, as well as monitoring internal control. This research method is a qualitative descriptive study with an interpretive approach where data collection is carried out by interview, observation, and documentation study. The data analysis technique used is the Miles and Huberman model analysis technique. The results of this study indicate that of the five elements, the Regional Government of Cimahi City has only implemented the elements of information and communication as well as internal control monitoring, while the other three elements have not been implemented adequately because all parameters have not been implemented due to implementation constraints, namely lack of socialization, inadequate implementation. risk assessment, evaluation and documentation activities that have not been maximal, as well as a lack of commitment to the implementation of SPIP.